ANALISIS KINERJA KEUANGAN BERDASARKAN RASIO LIKUIDITAS, SOLVABILITAS DAN RENTABILITAS PADA KOPERASI SIMPAN PINJAM SH JAYA MANDIRI KABUPATEN SIDENRENG RAPPANG - Ilham, Ilham; Arfianty, Arfianty (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2022)
The purpose of this study is to find out how the financial performance is based on the ratio of liquidity, solvency, and profitability at the SH Jaya Mandiri savings and loan cooperative, Sidenreng Rappang Regency. The method used in this research is quantitative descriptive, explaining how financial performance is using the formula for liquidity, solvency, and profitability ratios. The results of this study are that the SH Jaya Mandiri Savings and Loans cooperative has been good in paying attention to managing liquidity and solvency has been good for the past 5 years but it needs to be emphasized to further maximize the level of ROI and ROE to gain profits for the welfare of the members of the SH Jaya Mandiri Savings and Loans Cooperative. By conducting periodic performance appraisals, of course, it will make it easier for management to make decisions in the future. The provision of financing to customers or members must be more closely observed, although based on trust. You can use the 5C assessment of members or customers who need financing. And also in reporting it must be by the initial contract/agreement, if necessary go directly to avoid fraud and in terms of capital use, more attention should be paid so that the use of investment capital is not excessive on borrowing, because it will result in a decrease in profitability (profit) and it is feared that there will be difficulties in borrowing. the return.